POTENCY OF RADICAL SCAVENGING ACTIVITY FROM ETHYL ACETATE FRACTION OF Phaseolus vulgaris L., N. lappaceum L., and Pleurotus ostreatus - Anif Nur Artanti; Nestri Handayani; Nisya Arienda; Rika Triyoga Prasetyo Rini; Astrid Octaviani (Universitas Sebelas Maret, 2016)
Several studied shows that some plants and part of them could protect human body from oxidation of lipid and free radical danger exposure. Various possibilities can occur as a result of the free radical danger exposure, including malfunctioning of cells, damage cell structures, until the occurrence of cancer. One of the compounds found effication as an antioxidant is flavonoid. This study has been done to examine ethyl ascetate fraction from Phaseolus vulgaris L., N. lappaceum L., andPleurotus ostreatus which has potency as radical scavenger. Antiradical activity assay was determined by DPPH method (1,1 difenil-2-pikrilhidrazil). Based on the study the radical scavenging activity respectively from the lowest to the highest activity are vitamin C (5,4 µg/ml) ; fraction from Nephelium lappaceum L (21,81µg/ml) ; fraction from Phaseolus vulgaris L (50,64µg/ml) and Pleurotus ostreatus(80,51µg/ml).